Frequent ATRX mutations and loss of expression in adult diffuse astrocytic tumors carrying IDH1/IDH2 and TP53 mutations - Liu, Xiao-Yang; Korshunov, Andrey; Jones, David T. W.; Kool, Marcel; Pfister, Stefan (Acta neuropathologica, 2012)
Gliomas are the most common primary brain tumors in children and adults. We recently identified frequent alterations in chromatin remodelling pathways including recurrent mutations in H3F3A and mutations in ATRX (α-thalassemia/mental-retardation-syndrome-X-linked) in pediatric and young adult glioblastoma (GBM, WHO grade IV astrocytoma). H3F3A mutations were specific to pediatric high-grade gliomas and identified in only 3.4 % of adult GBM. Using sequencing and/or immunohistochemical analyses, we investigated ATRX alterations (mutation/loss of expression) and their association with TP53 and IDH1 or IDH2 mutations in 140 adult WHO grade II, III and IV gliomas, 17 pediatric WHO grade II and III astrocytomas and 34 pilocytic astrocytomas. In adults, ATRX aberrations were detected in 33 % of grade II and 46 % of grade III gliomas, as well as in 80 % of secondary and 7 % of primary GBMs. They were absent in the 17 grade II and III astrocytomas in children, and the 34 pilocytic astrocytomas. ATRX alterations closely overlapped with mutations in IDH1/2 (p < 0.0001) and TP53 (p < 0.0001) in samples across all WHO grades. They were prevalent in astrocytomas and oligoastrocytomas, but were absent in oligodendrogliomas (p < 0.0001). No significant association of ATRX mutation/loss of expression and alternative lengthening of telomeres was identified in our cohort. In summary, our data show that ATRX alterations are frequent in adult diffuse gliomas and are specific to astrocytic tumors carrying IDH1/2 and TP53 mutations. Combined alteration of these genes may contribute to drive the neoplastic growth in a major subset of diffuse astrocytomas in adults.